CosR Regulation of perR Transcription for the Control of Oxidative Stress Defense in Campylobacter jejuni - Myungseo Park; Sunyoung Hwang; Sangryeol Ryu; Byeonghwa Jeon (Microorganisms, 2021)
Oxidative stress resistance is an important mechanism to sustain the viability of oxygen-sensitive microaerophilic Campylobacter jejuni. In C. jejuni, gene expression associated with oxidative stress defense is modulated by PerR (peroxide response regulator) and CosR (Campylobacter oxidative stress regulator). Iron also plays an important role in the regulation of oxidative stress, as high iron concentrations reduce the transcription of perR. However, little is known about how iron affects the transcription of cosR. The level of cosR transcription was increased when the defined media MEMα (Minimum Essential Medium) was supplemented with ferrous (Fe2+) and ferric (Fe3+) iron and the Mueller–Hinton (MH) media was treated with an iron chelator, indicating that iron upregulates cosR transcription. However, other divalent cationic ions, such as Zn2+, Cu2+, Co2+, and Mn2+, did not affect cosR transcription, suggesting that cosR transcription is regulated specifically by iron. Interestingly, the level of perR transcription was increased when CosR was overexpressed. The positive regulation of perR transcription by CosR was observed both in the presence or in the absence of iron. The results of the electrophoretic mobility shift assay showed that CosR directly binds to the perR promoter. DNase I footprinting assays revealed that the CosR binding site in the perR promoter overlaps with the PerR box. In the study, we demonstrated that cosR transcription is increased in iron-rich conditions, and CosR positively regulates the transcription of PerR, another important regulator of oxidative stress defense in C. jejuni. These results provide new insight into how C. jejuni regulates oxidative stress defense by coordinating the transcription of perR and cosR in response to iron.